The ethical status of social impact bonds - Morley, Julia (2019)
I develop a framework for assessing the ethical status of social impact bonds (SIBs), drawing on evidence from UK and US SIBs that address recidivism, education, homelessness and healthcare. I extend work on the ethics of markets by Debra Satz to render it suitable for application to SIBs, highlighting informational weaknesses, power imbalances and the generation of harm. Ethical issues observed include the lack of informed consent, denial of care, prioritisation of profit over therapeutic effectiveness and unfair contracting. I find that SIBs are morally permissible in principle but are at great risk of becoming unethical in practice